IMPROVING THE METHODOLOGY OF INCREASING ECOLOGICAL CULTURE IN STUDENTS ON THE EXAMPLE OF GENERAL PEDAGOGY (Universal International Scientific Journal, 2026)
The sharpening of the balance between nature and society poses the task of developing ecological thinking in students to the higher education system. This study is aimed at identifying effective didactic opportunities for the formation of ecological culture in students using the example of the subject "General Pedagogy". In the course of the research, interactive methods such as case studies, problem situations and project-based learning (PBL) in ecological content were tested. The results showed that the integration of theoretical topics of pedagogical science with global and local environmental problems has a positive effect on the development of students' ecological thinking and practical skills. Based on the research, practical recommendations were developed for the formation of ecological competencies in pedagogical education.
Keywords: ecological culture, general pedagogy, didactic provision, interdisciplinary integration, project education, ecological competence, practical skills, pedagogical experience-testing.